Recent evolution in imaging techniques for assessment of synovitis in osteoarthritis - Hayashi, Daichi; Tu, Kevin; Roemer, Frank W.; Guermazi, Ali (Skeletal Radiology, 2025)
Synovitis remains an important marker of osteoarthritis (OA) disease incidence and progression, and is best assessed using imaging. In general, MRI with intravenous contrast is considered the gold standard method for assessing synovitis because it can effectively differentiate inflamed synovium and adjacent joint effusion and other surrounding structures. However, administration of intravenous gadolinium is not always desirable. Several emerging methods are being explored for the visualization of synovitis using non-contrast-enhanced MRI (NCE-MRI) but currently underestimate the amount of inflammation. Ultrasound is another approach that is able to measure and quantify synovitis; however, as with other applications of ultrasound, it is observer-dependent, which may affect reproducibility. Radiography does not play a role in synovitis assessment due to its inability to differentiate intraarticular soft tissues. CT, when contrast enhanced, has been shown to effectively detect synovitis and may be a viable alternative to MRI when MRI is contraindicated or not available. Nuclear medicine techniques such as PET-CT, PET-MRI, and SPECT-CT are not routinely used due to high cost, radiation exposure, and image acquisition times. However, novel radiotracers/biomarkers are being investigated. AI approaches have been investigated for their ability to predict clinical and structural outcomes and for automated detection and quantification including features such as effusion-synovitis.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Imaging; MRI; Osteoarthritis; Synovitis; Ultrasound